Contribuições para a pirólise da casca de macadâmia em leito de jorro cônico - Xavier, Thiago Padovani (2016)
Pyrolysis is a promising technology for renewable energy generation since it can generate products (charcoal, bio-oil and gas) with high calorific value from agro-industry wastes, such as macadamia nuts shell. Although there are some plants operating on an industrial scale, the biomass pyrolysis process is relatively recent, with several weaknesses that need to be overcome. The understanding of the pyrolysis process involves the study of biomass degradation kinetics as well as the type, configuration, and operation conditions of reactor. Thus, the main objective of this work was to contribute to some key aspects of pyrolysis of macadamia shell in conical spouted bed, that are very important for the process optimization. The pyrolysis kinetics of macadamia shell was investigated from experimental thermogravimetric data. The parameters of two of the main kinetic models available in the literature were estimated. The simulated results show that the model of Independent Parallel Reactions is what best represents the mass loss of biomass during pyrolysis. The activation energy values estimated for each component were: extractives (193-202 kJ/mol), hemicellulose (125-140 kJ/mol), cellulose (226-262 kJ/mol) and lignin (62-77 kJ/mol). With respect to the reactor, the conical spouted bed, fluid dynamic analysis of the behavior of mixture of macadamia shell and sand was performed, evaluating how static bed height (0.06, 0.08 and 0.10m) and mass fraction of biomass (25, 50 and 75%) influence on minimum spouting condition and particle segregation. It was found that the beds with largest heights are heavier, resulting in higher pressure drop and air velocity to keep the regime spouted. Furthermore, higher biomass mass fractions give higher porosity to the bed in the annular region, which reduces the flow resistance of the fluid, decreasing the air velocity and pressure drop in the minimum spouting condition. The segregation of the mixture was higher in the base of the bed, with predominance of sand in this region. By having smaller density and diameter, macadamia shell is more easily entrained into the top of the bed. In other regions, for all conditions studied, it was found acceptable levels of segregation for a biomass pyrolysis process. Finally, the identification of components of vapors generated during the fast pyrolysis (analytical micro-pyrolysis) allowed characterizing bio-oil generated at temperatures of 450, 550 and 650°C. It identified the presence of highly non-polar and intermediate polarity molecules, such as aliphatic hydrocarbons, normal and branched chain (paraffins), alicyclic hydrocarbons (cycloparaffins), olefins (normal, branched and cyclic) and aromatic (simple, polycyclic and substituted), and other chemical compounds of industrial interest.